Influence of a neurokinin‐1 receptor antagonist (aprepitant) on gastric sensorimotor function in healthy volunteers. Issue 12 (2nd September 2013) - Ang, D.; Pauwels, A.; Akyuz, F.; Vos, R.; Tack, J.
Abstract Background Substance P (SP) is a member of the neurokinin (NK) family and is one of the established neurotransmitters in the mammalian central and enteric nervous system. It is unclear whether NK1 receptors are involved in the control of gastric sensorimotor function in man. Methods We studied the effects of aprepitant, an NK1 receptor antagonist used in the treatment of chemotherapy‐induced emesis, on gastric sensorimotor function in healthy volunteers. Sixteen healthy volunteers (six males, 32.4 ± 2.7 years) were studied on three separate occasions after placebo, aprepitant 80 or 125 mg in randomized double‐blind study to assess gastric compliance, perception to isobaric distensions, and gastric accommodation with a gastric barostat. Key Results Compared to placebo, both doses of aprepitant did not influence gastric compliance or sensitivity to gastric distension. Aprepitant 80 and 125 mg did not have any significant effects on gastric accommodation compared with placebo (mean postprandial gastric volume increase, respectively, 83.4 ± 28.4 vs 35.3 ± 16.2 vs 83.9 ± 30.4 mL, NS). Postprandial gastric compliance and sensitivity to distention were also not altered. Conclusions & Inferences In health, NK1 receptors do not appear to be involved in the control of gastric compliance, accommodation or sensitivity to distention in man.